COMPARISON OF ALTERNATIVE PERIPHERAL AND TRANSCATHETER AORTIC VALVE REPLACEMENT : SYSTEMATIC REVIEW - Sabri, Muhammad; Nasution, Faisal Syahroni; Namora Siregar, Aulia Doli; Sutrisno, Reza Tri; Arifin Rambe, Zainal; Fadilla, Annisa Tria (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Transcatheter aortic valve replacement (TAVR) is approved for use in low-to-extreme-risk patients with aortic stenosis, with volumes exceeding those of surgical aortic valve replacement and outcomes continuing to improve. The transfemoral (TF) access route is accepted as the first choice for TAVR and accounts for 95 of cases. However, the use of alternative access remains relevant in many patients with peripheral vascular disease or unfavorable anatomy. The aim: This study aims to show about comparison of alternative peripheral and transcatheter aortic valve replacement. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 135 articles, whereas the results of our search on SagePub brought up 118 articles. The results of the search conducted for the last year of 2013 yielded a total 56 articles for PubMed and 33 articles for SagePub. The result from title screening, a total 16 articles for PubMed and 10 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria. Conclusion: To compare outcomes among transcatheter aortic valve replacement (TAVR) performed via transaortic (TAo) and subclavian (SCL) approaches. Many patients are not amenable for TAVR via the transfemoral route due to peripheral vascular disease. Limited data exist regarding safety and procedural feasibility of TAVR via TAo and SCL routes.